2019
DOI: 10.1001/jamanetworkopen.2018.6694
|View full text |Cite
|
Sign up to set email alerts
|

Association of Childhood Social-Emotional Functioning Profiles at School Entry With Early-Onset Mental Health Conditions

Abstract: Key Points Question What can population patterns of early childhood social-emotional functioning tell us about the emergence of mental health conditions? Findings In this cohort study that included 34 323 children in Canada, 6 latent social-emotional functioning profiles based on children’s relative strengths and vulnerabilities in social competence, internalizing, and externalizing symptoms at age 5 years were associated with the onset of subsequent mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 73 publications
1
25
0
2
Order By: Relevance
“…Socioemotional competence is a key predictor of social and academic success, and challenges with socioemotional functioning in early childhood have consequences for long-term social, academic success and mental health [ 221 223 ]. Early socioemotional competence in kindergarten is correlated with lower probability of mental health issues in adolescence; and higher probability of graduating from high school, attending college, being employed in adulthood [ 222 , 224 ]. Conversely, lower socioemotional competence in preschool is linked to higher internalizing (e.g., depressed mood, anxiety, social withdrawal) and externalizing (e.g., aggression, hyperactivity) symptoms in adolescence [ 225 ].…”
Section: Discussionmentioning
confidence: 99%
“…Socioemotional competence is a key predictor of social and academic success, and challenges with socioemotional functioning in early childhood have consequences for long-term social, academic success and mental health [ 221 223 ]. Early socioemotional competence in kindergarten is correlated with lower probability of mental health issues in adolescence; and higher probability of graduating from high school, attending college, being employed in adulthood [ 222 , 224 ]. Conversely, lower socioemotional competence in preschool is linked to higher internalizing (e.g., depressed mood, anxiety, social withdrawal) and externalizing (e.g., aggression, hyperactivity) symptoms in adolescence [ 225 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the significant impact that emotional and behavioral functioning can have on child readiness and later achievement (e.g., Quirk et al, 2016; Woodward et al, 2016), further research should include evaluation of these domains of human development (Thomson et al, 2019). Duncan et al (2007) showed that measures of socioemotional behaviors, including internalizing and externalizing problems and social skills, were generally non-significant predictors of later academic performance, even among children with relatively high levels of problem behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded two studies that used six different longitudinal data sets (Duncan et al, 2007;Grissmer et al, 2010) that could not be used to answer aims (2) and (3). One article that analyzed only social-emotional function or mental health were also excluded (Thomson et al, 2019). The final sample for data extraction consisted of 13 articles.…”
Section: D) Data Extractionmentioning
confidence: 99%
“…The purpose of the instrument is to report, at a population-level, children's school readiness [27]. The instrument's validity and reliability has been consistently demonstrated among different groups of children [28][29][30][31] including those with English-as-a-Second-Language [32].…”
Section: Data Sourcesmentioning
confidence: 99%